Collective interviewing: the use of a model statement to differentiate between pairs of truth-tellers and pairs of liars - Vernham, Zarah (Legal and criminological psychology, 2018)
Purpose. The current experiment examined the use of a model statement for aiding lie detection and gathering additional information during interviews in which pairs of suspects were interviewed together (i.e., collective interviewing). A model statement is an example of an answer, unrelated to the topic under investigation, which is played to suspects to demonstrate how much information the interviewer wants them to provide in response to the question asked. Method. Pairs of truth-tellers visited a restaurant together, whereas pairs of liars completed a mock crime. The task for all pairs was to convince an interviewer that they were visiting a restaurant together at the time the crime was committed. Half the truth-telling pairs and half the lying pairs were exposed to a model statement, whilst the other halves were not. Results. Truth-telling pairs were more detailed and showed more interactions than lying pairs, particularly in the model statement present condition. Conclusions. Being exposed to a model statement in a collective interview magnified the differences between pairs of truth-tellers and pairs of liars in reporting detail and interacting with one another. A model statement is simple to implement and can be applied to many real-world investigative interviewing settings whereby the focus is on lie detection and gathering as much information as possible.